Evidence assessing the development, evaluation and implementation of digital health technologies in wound care: A rapid scoping review. Issue 4 (November 2022) - Shi, Chunhu; Dumville, Jo C.; Juwale, Harun; Moran, Connor; Atkinson, Ross
Abstract: Objective: To scope published data on the development, evaluation and implementation of digital health technologies for use in wound care. We focused on digital health technologies that supported one or more of the following functions: system level (such as electronic health records, management systems), wound imaging and measurement, and communication. Methods: For this rapid scoping review, Ovid MEDLINE and Ovid Embase were searched in January 2021 and relevant experts were consulted. We identified English language publications that reported the development, evaluation, and/or implementation of relevant digital health technologies. Studies were screened and data extracted and coded following the established scoping review methodology. Data were presented narratively, and in tabular formats. Results: We included 156 studies in the review. After reported technologies were categorised based on their predominant function, 51 (32.7%) studies reported on system level technologies; 123 (78.8%) on wound imaging and measurement technologies; and 34 (21.8%) on communication-focused technologies such as video-conferencing technologies, messaging technologies). Of the 156 studies, 37 (23.7%) reported data on development of the technology; 135 (86.5%) reported evaluation activities, mainly for wound imaging and measurement technologies; and 2 (1.3%) reported implementation research. Conclusion: There is increasing focus on digital health technologies in wound care. Assessment of digital health technologies aimed at wound care has mainly been for those with a primary function around wound imaging and measurement. Most studies reported evaluation whilst evidence suggests the field may lack transparent reporting of technology development and implementation activities that could aid further decision-making. Highlights: The scoping review mapped evidence on the development, evaluation and implementation of wound care digital technologies. Literature in this field has mainly been for technologies with a primary function around wound imaging and measurement. Most literature reports evaluation of digital health technologies. This field lacks literature on technology development and implementation activities that could aid further decision-making. technology development and implementation activities that could aid further decision-making.